2020
DOI: 10.3390/ijerph17197288
|View full text |Cite
|
Sign up to set email alerts
|

Beach Tourism in Times of COVID-19 Pandemic: Critical Issues, Knowledge Gaps and Research Opportunities

Abstract: The strict quarantine measures employed as a response to the COVID-19 pandemic have led the global tourism industry to a complete halt, disrupting the livelihoods of millions. The economic importance of beach tourism for many destinations has led many governments to reopen tourist beaches, as soon as the number of infection cases decreased. The objective of this paper is to provide a scientific basis for understanding the key issues for beach tourism management in these circumstances. These issues include risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 100 publications
2
72
0
11
Order By: Relevance
“…In addition, the policy of social distancing implemented by most countries has resulted in the cleaning of beaches, as tourists accumulate waste when visits the beaches (Zielinski and Botero 2020). A significant reduction in noise levels has also been observed.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the policy of social distancing implemented by most countries has resulted in the cleaning of beaches, as tourists accumulate waste when visits the beaches (Zielinski and Botero 2020). A significant reduction in noise levels has also been observed.…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, the COVID-19 pandemic has resulted in 82,401,834 confirmed cases and 1,801,280 deaths so far, based on the data available up to December 31st. In an attempt to stem the advance of the disease, governments around the world have implemented preventive measures such as lockdowns, strict social distancing, and travel bans, which have resulted in estimated economic losses of hundreds of billions of dollars, in particular in the tourism sector, which was severely affected ( Ormaza-González and Castro-Rodas, 2020 ; Zielinski and Botero, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The literature review has shown that political and health crises generate instability and a significant impact on the tourism industry [6,62,63], generating negative effects such as the decrease in visitors that has resulted in low economic income. There is evidence of cases that have gone through similar episodes and have never been able to recover, but there is also evidence of destinations that have applied good strategies and their recovery has been evident [32,40].…”
Section: Discussionmentioning
confidence: 99%
“…Due to global border closures, tourism has been one of the sectors most affected by the coronavirus pandemic [5]. The crisis is unprecedented in size and scope, and has affected the livelihoods of millions of people around the world [6,7]. In this period, USD 320 billion in tourism exports were lost, more than triple the losses during the global financial crisis of 2009 [8].…”
Section: Introductionmentioning
confidence: 99%